Simplified Design of Low-Delay Oversampled NPR GDFT Filterbanks - Dumitrescu, Bogdan; Bregović, Robert; Saramäki, Tapio (EURASIP journal on advances in signal processing, 2006)
: We propose an efficient algorithm for designing the prototype filters of oversampled, near-perfect reconstruction (NPR), GDFT modulated filterbanks (FB) with arbitrary delay. We describe simplified conditions for imposing NPR, posed on the frequency response of the distortion transfer function and on the stopband attenuation of the prototype filters. Given the analysis prototype, we show that the minimization of the stopband energy of the synthesis prototype, subject to the simplified NPR constraints, can be expressed as a convex optimization problem. Our algorithm consists of initialization with the prototype of a near-orthogonal FB-which can also be designed via convex optimization-and then successive optimization of the synthesis and analysis prototypes. We give design examples, discuss the properties of the obtained FBs, and present synthetic echo control experiments. The presented results show that, for a given delay, our algorithm produces FBs with significantly better properties than the near-orthogonal FBs.